The interest of oral calcium loads test in the diagnosis and management of pediatric nephrolithiasis with hypercalciuria: Experience from a tertiary pediatric centre. Issue 4 (August 2020) - Mosca, Mélodie; Bertholet-Thomas, Aurélia; Lemoine, Sandrine; Garnier, Charlotte; Machon, Christelle; Molin, Arnaud; Dubourg, Laurence; Bacchetta, Justine
Summary: Introduction: The use of calcium load has been forgotten in pediatrics until recently whereas it is of utmost importance to have a practical approach to guide management of hypercalciuric nephrolithiasis. Objective: The purpose of this study was to evaluate the practical interest of oral calcium loads to improve the overall management of nephrolithiasis in children. Methods: We retrospectively studied all pediatric patients having undergone an oral calcium load in our pediatric nephrology unit between September 2015 and April 2017. Results: A total of 16 patients were included, at a median age of 12.0 (5.5–17.5) years. The indications of oral calcium load were: presence of an active urolithiasis without any obvious explanation after ruling out the "classical" biological abnormalities, or presence of hypercalciuria with stones composed of weddellite or carbapatite crystals. Among the 16 patients, 6 (38%) patients displayed absorptive hypercalciuria, 2 (12%) renal leak, 3 (19%) "unclassified" inadapted PTH, and 5 (31%) a normal calcium load test. The result of oral calcium load modified the clinical management in 14 (88%) patients, mainly based on the type of hypercalciuria. It allowed us to individualize nutritional advice: in patients with absorptive hypercalciuria, we proposed calcium intake within the lower normal range for age with dairy products not enriched with vitamin D, with the advice to avoid salt and calcium loads during evenings. Conversely, in patients with resorptive hypercalciuria, we proposed normal calcium intake for age. Showing the results of the calcium load is meaningful to patients and parents, and can be considered as an "educational" tool. Discussion: To the best of our knowledge, this study is the first to evaluate the interest of calcium load in children with nephrolithiasis in an era of routine PTH and 1-25-D assessment. Here, we demonstrate the feasibility and safety of oral calcium load in children, its interest to understand the underlying mechanisms of hypercalciuria, and its major interest as an "educational tool" for patients to explain them the underlying mechanisms and thus guide the therapeutic management using an individualized dietary approach. This study did not include many patients, but to the best of our knowledge, this is the first study evaluating and validating the feasibility of a safe and non-expensive diagnosis tool in pediatric hypercalciuria. Conclusion: Oral calcium load is helpful to guide therapeutic adaptation in pediatrics using an individualized dietary approach. Summary Figure Image 1